An Analysis of Facade Transformation in Pasar Kayoon Surabaya - Sovie Nurmalia Junita; Darini Yusrina Abidah; Dian Kartika Santoso; Faiz Ramadiansyah (Program Studi Arsitektur, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2025)
Pasar Kayoon in Surabaya holds historical significance and a strategic position as a hub for the flower trade and other commercial activities in the city center. Over the past decade, the area has experienced notable physical and visual transformations, especially in its building facades, a key element of the area’s urban identity. This study analyzes facade development in the Pasar Kayoon area from 2015 to 2025 and identifies factors influencing these changes. An explanatory method with a qualitative descriptive approach was employed, using Google Street View terrestrial imagery for longitudinal observation from a pedestrian perspective. Visual and spatial analyses focused on facade elements,form, materials, colors, signage, and forecourt use,triangulated with maps, photographic documentation, and historical literature. Findings indicate significant changes in some segments, including conversion of open spaces into kiosks, signage redesign, facade element modifications, and building height alterations, while other segments maintained their original character with minor adjustments. These transformations were driven by commercial needs, changes in sold commodities, space demands for economic growth, and contemporary design trends. The study provides insights for maintaining visual cohesion while preserving the area’s historical identity in future development planning